2018
DOI: 10.1007/s00595-018-1649-4
|View full text |Cite
|
Sign up to set email alerts
|

APC:T1556fs and STK11 mutations in duodenal adenomas and adenocarcinomas

Abstract: APC:T1556fs and STK11 mutations found in duodenal adenomas/ACs highlight the importance of proteins encoded by these genes in tumor development. APC mutations were identified in duodenal adenomas more frequently than in duodenal ACs, which differed from the observations of typical adenoma-carcinoma sequences seen in colorectal cancer, suggesting the limited involvement of this mechanism in duodenal cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…Interestingly, we detected APC mutations (55%) more frequently in early non-ampullary duodenal lesions than did earlier studies in advanced lesions, which reported frequencies of 13-27% in SBAs or 8% in DAs [17,[20][21][22]. Kojima et al separately analyzed multiple components in non-ampullary duodenal lesions that exhibited different histological grades, and observed APC mutations more frequently in the adenoma (58%) than in the adenocarcinoma (25%) components [24]. The earlier observation that abnormal nuclear localization of β-catenin is more frequent in non-ampullary duodenal adenomas than in adenocarcinomas (84% versus 33%) may support these results [26].…”
contrasting
confidence: 51%
See 3 more Smart Citations
“…Interestingly, we detected APC mutations (55%) more frequently in early non-ampullary duodenal lesions than did earlier studies in advanced lesions, which reported frequencies of 13-27% in SBAs or 8% in DAs [17,[20][21][22]. Kojima et al separately analyzed multiple components in non-ampullary duodenal lesions that exhibited different histological grades, and observed APC mutations more frequently in the adenoma (58%) than in the adenocarcinoma (25%) components [24]. The earlier observation that abnormal nuclear localization of β-catenin is more frequent in non-ampullary duodenal adenomas than in adenocarcinomas (84% versus 33%) may support these results [26].…”
contrasting
confidence: 51%
“…A customized panel, encompassing all exons for 75 cancer-related genes including those frequently mutated in SBAs [17][18][19][20][21]33,34], was created using the Ion Ampli-Seq Designer (Thermo Fisher Scientific) (supplementary material, Table S2). Genes whose mutations had been reported in duodenal adenomas were also included [24]. The assay design consisted of 3663 amplicons with an average length of 112 bp, covering 95.5% of the 366 kb target sequence.…”
Section: Targeted Amplicon Sequencing Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A mutation cluster region (MCR) in exon 15 of APC 99, covering mainly the β-catenin-binding functional domain of APC, has been identified as a site with higher mutation rates, including gene deletions occurring in c.39273931delAAAGA and c.31833187delACAAA, and site mutations occurring in exon 15, c.1744G>A, or c.1744G>T 97, 100 (Figure 2A). Besides, according to a study by Kojima et al, APC and STK11 mutations found in duodenal adenomas/adenocarcinomas highlight the importance of proteins encoded by these genes in tumor development 75. Mutations in MUTYH have also been associated with FAP in special cases of recessive genetic FAP 101.…”
Section: Fap Susceptibility Genes and Mechanism Of Actionmentioning
confidence: 99%